Revitalisasi Kawasan Alun-Alun Kota Tegal Tahun 2019 - A'yunina, Isna (Journal of Indonesian History, 2023)
ABSTRACT The town square area is one of the public spaces that can be utilized by the entire community as a place for various activities, such as religious activities, memorial ceremonies, festivals, sport activities, or just a place for recreation. The city government revitalized the square area and the pancasila street area. The condition was due to the fact that situation in the area was less organized and looked rundown. This study aims to examine and analyze the effects on informal workers in the square and surrounding areas after the revitalization project. This research uses historical research methods. Data collection conducted in this research is through searching for written sources, conducting field observations, documentation and conducting interviews with related parties. The results of this study indicate that the revitalization project in the alun-alun area and the Pancasila Street area which functions as a public space has been carried out quite well, but not maximally. This is reflected in (1) The planning of the revitalization project launched by the city government in the square area has not been maximized, this is considering the function of Tegal City square over time (2) There are some informal workers who get unfavorable influences such as a drastic decrease in income after the revitalization project (3) There are also some informal workers who suffer from the loss of income. Keywords: Revitalization, Town Square, Tegal City